The Halal Industry As A Support System For Sustainable Development Goals In The Society 5.0 Era - Hikmatul Hasanah, Hikmatul Hasanah (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
This paper presents insights about halal as a global industry support system and how the halal industry can play its role in the world's mega project events; Sustainable Development Goals in the era of society 5.0 which demands synergy between humans and technology in various activities, this topic is raised as an effort to connect the halal industry with the Sustainable Development Goals and halal from global problems related to the failure to transform development into human and universal welfare. This paper uses a literature review as a summary of the relevant theories. With halal as an industrial paradigm, humans do not only carry out economic activities with the motive of meeting needs and taking profits without being based on ethics. Keywords:halal, halal industry, Sustainable Development Goals, era of society 5.0